Callus growth of red starfruit (Baccaurea angulata) leaves with the addition 2,4-D (dichlorophenoxy acetic acid) and kinetin - Zulfa Zakiah; Murni Murni; Masnur Turnip (Symbiotic: Journal of Biological Education and Science, 2024)
One of the obstacles to propagating red starfruit (Baccaurea angulata) using seeds is that fruit without seeds is often found. Tissue culture is an alternative for propagating red star fruit plants to provide seeds or secondary metabolites through callus culture. The research aims to determine the effect of 2,4-D and kinetin on callus growth of star fruit leaves and to obtain the best concentration to induce callus. This research used a factorial Completely Randomized Design (CRD) with two treatment factors, namely 2,4-D (0; 0.5; 1.0; 1.5; 2.0; 2.5 ppm) and kinetin (0; 0.5; 1.0; 1.5; 2.0; 2.5 ppm). The observation parameters consisted of callus emergence time (days after planting), wet and dry weight of the callus (g), color and texture of the callus. The results showed that the combination of 2,4-D and kinetin had a significant effect to callus emergence time, but didn't on the wet and dry weight of the callus. The fastest callus emergence time was obtained of 2.5 ppm 2,4-D + 0.5 ppm kinetin, 1.5 ppm 2,4-D + 2.5 ppm kinetin namely 6 DAP. The callus color is white, brown, and brown with a friable and compact texture. Another response that emerged was root growth.